Different Technical Variables Affecting Noni (Morinda Citrifolia L.) Wine Fermentation - N. P. Minh (Journal of Global Pharma Technology, 2016)
Noni (Morinda citrifolia L.) is one of the most important fruit which was widely used for its health restorative properties. It has been used an herbal medicine in various ailments. This fruit is considered a natural antioxidant. It can prevent cancer, heart disease, diabetes, cognitive dysfunction, hypertension etc., and maintain overall good health. Over the years, its popularity has been diminished due to unpleasant smell from the ripened fruit. There is limited study mentioning to processing of this functional fruit. Therefore we explored a wine fermentation from noni fruit by focusing on the effect of different variables such as sugar supplementation, yeast ratio inculation, fermentation time and temperature in the primary fermentation, and fermentation time and temperature in the secondary fermentation to noni wine quality (%v/v alcohol; g/l acidity; oBrix residual sugar; sensory score). Our results proved that the primary fermentation should be conducted with 15% sugar supplementation, 0.15% Sacchromyces cerevisiae at temperature 29.0oC in 10 days. The secondary fermentation was adequate in 9.5oC for 3 weeks to get a pleasant flavor and aroma. Noni wine also evaluated the antioxidant capacity and total phenolic content. Noni wine could be considered as a good source of antioxidants and phenolics ideal for daily healthy consumption.Keywords: Noni, Wine, Fermentation, Sacchromyces cerevisiae, Antioxidant, Phenolic.